2022
DOI: 10.3390/biom12060781
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the miR-200 Family: A Clan of Five Siblings with Essential Roles in Development and Disease

Abstract: Over two decades of studies on small noncoding RNA molecules illustrate the significance of microRNAs (miRNAs/miRs) in controlling multiple physiological and pathological functions through post-transcriptional and spatiotemporal gene expression. Among the plethora of miRs that are essential during animal embryonic development, in this review, we elaborate the indispensable role of the miR-200 family (comprising miR-200a, -200b, 200c, -141, and -429) in governing the cellular functions associated with epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 231 publications
0
4
0
Order By: Relevance
“… 49 Another study found that miR-200b and miR-200c play a role in neurodegenerative diseases by targeting genes that cause progressive degeneration of the structure of the central nervous system. 50 These results suggest that RBCs contribute to modulation of the immune response during P. falciparum infection; however, the mechanism underlying this process is currently unknown.…”
Section: Discussionmentioning
confidence: 97%
“… 49 Another study found that miR-200b and miR-200c play a role in neurodegenerative diseases by targeting genes that cause progressive degeneration of the structure of the central nervous system. 50 These results suggest that RBCs contribute to modulation of the immune response during P. falciparum infection; however, the mechanism underlying this process is currently unknown.…”
Section: Discussionmentioning
confidence: 97%
“…miR-200c and miR-141 are members of the miR-200 family, which also includes miR-200a, miR-200b, and miR-429. These miRNAs are involved in advanced stages of cancer progression, and they might act as activators or suppressors of tumorigenesis [28]. Via pathway analysis of potential mRNAs targets of miR-200 family members, we observed upregulation of epidermal growth factor receptor (EGFR), mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) signaling.…”
Section: Discussionmentioning
confidence: 99%
“…By combining with the nucleolin receptor, Tipα induces mesenchymal phenotype switch leading to cancerogenesis [ 182 ]. It has been also shown that Hp initiates EMT via the upregulation of ZEB1 and microRNA (miR)-200 [ 183 ]. Finally, TGF-β has been considered one of the most potent among EMT inducers.…”
Section: Caf Sourcesmentioning
confidence: 99%
“…In the metastatic cascade, miR-200 exerts a context-dependent role. In general, the expression of miR-200 family members in the primary tumor strengthens an epithelial phenotype, thereby preventing EMT; nevertheless, miR-200s also support MET at distant organ sites, thereby promoting metastatic colonization [ 183 ]. miR-141 was shown to directly target and repress TGF-β2, thus promoting epithelial phenotype in TGF-βRII-expressive cell line [ 347 , 348 ], whereas TGF-β1 evoked transcriptional repression of miRNA-200 family genes through the regulation of histone H3 methylation [ 347 , 349 ].…”
Section: The Influence Of Cafs On Gastric Stem Cell Niche and Cancer ...mentioning
confidence: 99%